Implementation of Problem Based Learning Model in Improving Student Learning Outcomes in Islamic Religious Education Learning at SD Negeri 0202 Binanga - Patimah; Siregar, Erlina (Journal of Media and Learning Technology, 2025)
This study aims to improve student learning outcomes in Islamic Religious Education learning on the subject of respect for teachers in grade IV students of SD Negeri 0202 Binanga through the application of problem-based learning methods. This study is a Classroom Action Research (CAR) using a problem-based learning model that is implemented in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The subjects of the study were 24 grade IV students. Data were collected using observation sheets, questionnaires, and field notes. The results showed an increase in the attitude of respecting teachers from Cycle I to Cycle II. In Cycle I, 60% of students showed an increase in the attitude of respecting teachers, while in Cycle II the percentage increased to 85%. The success factors of this study include the application of moral values ​​consistently, teacher role models, and reflection activities and direct practice in learning. This study concludes that the learning method based on moral values ​​is effective in improving the attitude of respecting teachers. Therefore, this method is recommended for use in Islamic Religious Education (PAI) learning to shape better student character.